OPENEOX: A MACHINE-READABLE FRAMEWORK FOR STANDARDIZED END-OF-LIFE SOFTWARE MANAGEMENT - Дем'янчук, Сергій (SWorldJournal, 2025)
The exponential growth of software dependencies in modern infrastructure has created critical gaps in lifecycle information management, particularly regarding End-of-Life (EoL) status determination and automated processing. Building upon established resea